The MARK-AGE extended database: data integration and pre-processing. (November 2015) - Baur, J.; Kötter, T.; Moreno-Villanueva, M.; Sindlinger, T.; Berthold, M.R.; Bürkle, A.; Junk, M.
Highlights: The objective of the MARK-AGE study was to identify biomarkers of human aging. During the study, the necessity of extending the database became apparent. Pre-processing steps were applied to the data to ensure high data quality. Abstract: MARK-AGE is a recently completed European population study, where bioanalytical and anthropometric data were collected from human subjects at a large scale. To facilitate data analysis and mathematical modelling, an extended database had to be constructed, integrating the data sources that were part of the project. This step involved checking, transformation and documentation of data. The success of downstream analysis mainly depends on the preparation and quality of the integrated data. Here, we present the pre-processing steps applied to the MARK-AGE data to ensure high quality and reliability in the MARK-AGE Extended Database. Various kinds of obstacles that arose during the project are highlighted and solutions are presented.